Lake Prespa, Northwestern Greece : a Unique Balkan Wetland - Crivelli, Alain J. (Developments in hydrobiology, 1997)
Lakes in the Balkans are numerous, but few of them have been studied, and even fewer on a long-term basis. This book is the first on a lake of the Balkans since the monograph on Lake Ohrid (1956). It is a synthesis of our present knowledge on the ecology and functioning of the lake and its resources, with an emphasis on its endemism and on the management needed to preserve its unique fauna and flora. It also contains original long-term studies on pelicans and fish. The target readership is well-educated lay people, conservationists (especially birdwatchers) and wetland scientists.